Characterization of Cistus × incanus L. and Cistus ladanifer L. Extracts as Potential Multifunctional Antioxidant Ingredients for Skin Protecting Cosmetics - Katarzyna Gaweł-Bęben; Wirginia Kukula-Koch; Uliana Hoian; Marcin Czop (MDPI AG, 2020)
Skin is constantly exposed to harmful environmental factors, causing photo-oxidative stress in cells and leading to the development of health and aesthetic problems. Multifunctional ingredients of everyday skincare products, possessing antioxidant, UV-protecting, anti-hyperpigmentation, and skin cancer-preventing properties are in high demand. Due to the high content of polyphenolic compounds Cistus × incanus L. and Cistus ladanifer L. are potentially interesting sources of cosmetic ingredients with multiple skin protecting functions. In this study eight extracts from dried C. incanus and C. ladanifer—aerial parts were prepared using 60% (v/v) or 100% (v/v) methanol, on a magnetic stirrer or in Soxhlet apparatus, and compared for their content of phytochemicals and properties important for the skin protection. Extracts from C. incanus prepared in 60% (v/v) methanol contained the highest amount of polyphenolic compounds (331.82−347.27 mg GAE/g DW) and showed the most significant antioxidant activity (IC50 = 3.81−4.05 µg/mL). C. incanus extracts were also effective tyrosinase inhibitors (30−70% inhibition at 100 µg/mL). Statistical correlation analysis revealed that epicatechin, epigallocatechin gallate (EGCG), and myricitrin may be responsible for the antioxidant and tyrosinase inhibitory potential of C. incanus extracts. All analyzed extracts were cytotoxic for human melanoma cells A375 (IC50 = 57.80−199.01 µg/mL), with C. incanus extract prepared in 100% (v/v) methanol using Soxhlet extraction being the most effective. The extracts did not significantly impair the growth of noncancerous human keratinocytes HaCaT. C. incanus and C. ladanifer extracts possess also natural sun protecting activity (SPF 3.42−3.77 at 100 µg/mL), enhancing their anti-hyperpigmentation and anti-melanoma potential.